(untitled) (Al-Qamar, 2026)
Study has been conducted to explore the strategies of reinforcement which are used by the English language teachers in public school Mirpurkhas. Broadly, there are two types of reinforcement in behaviorism theory, and distinct teachers use multiple strategies for positive and negative reinforcement. This is a qualitative case study. Specifically, it is an exploratory case study, as it reveals the strategies for reinforcement in a specific context. Purposive sampling was used for the selection of participants; as only English language teachers were chosen, who had experience of at least two years, teaching. Furthermore, data were collected through two tools. One is a semi-structured interview protocol and second is an observation sheet for the triangulation of the data. Then the data were analyzed by using thematic analysis model of Braun and Clark 2006. Results of the study show that teachers use positive reinforcement and negative reinforcement in different ways. Conclusively, findings demonstrate diverse strategies for positive and negative reinforcement. Broadly those are verbal, non-verbal physical gifts and punishment.